Perencanaan pembelajaran Pendidikan Kewarganegaraan (PKn) untuk mengembangkan kesadaran bela negara mahasiswa - Sulkipani, Sulkipani (Jurnal Civics: Media Kajian Kewarganegaraan, 2017)
This study discusses how to design the Civic Education (CE) of learning plan to develop awareness of the student on country defense. The problem examined in this research was how to plan so it can build awareness of the student on country defense. This study used a qualitative research approach with the descriptive method. The techniques of data collection were interviews, observation, and study the documentation. Subject in the research consists of CE experts, the Professor of the Department of MKDU, and the students of various disciplines in the Education University of Indonesia (UPI). Research results revealed that the planning study has been designed in accordance with the provisions of the planning of learning in higher education, but still need development in some components such as methods, resources, and learning materials. The findings of the expert revealed that: planning study to be prepared and developed according to the characteristics of the students.